Pemberdayaan Siswa Dalam Edukasi Makanan Sehat & Bahaya Jajanan Sembarangan Pada Anak-Anak di SD Negeri 101826 Tuntungan - Siregar, Putra Apriadi; Fathin, Fadhilah Rahmadani; Siregar, Salwa Salsabila; Harahap, Sandrina Aulia; Azzahra, Sheylla; Sifa, Syalsabila (CV. Rayyan Dwi Bharata, 2025)
-